PENGARUH MODEL PEMBELAJARAN COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) TERHADAP HASIL BELAJAR BAHASA INDONESIA MATERI BERTUKAR DAN MEMBAYAR KELAS IV DI SD NEGERI NGRANDULOR 1 - Anjar Sinta Dewi; Emy Yunita Rahma Pratiwi (JURNAL ILMIAH NUSANTARA, 2025)
This research aims to examine the effectiveness of the CIRC (Cooperative Integrated Reading and Composition) learning model in improving students' learning outcomes. The CIRC model is a group-based learning approach that allows students to actively engage in discussions and be fully involved in the learning process with their peers. This approach not only creates variation in teaching methods but also helps students discover new learning strategies that can be applied during lessons. Through this structured approach, students are given the opportunity to develop their understanding through hands-on group experiences, group discussions, listening to explanations, and engaging in critical thinking activities. The literature review method was used in this study to explore the effectiveness and application of the CIRC model. The findings indicate that the implementation of this model significantly improves students' understanding and engagement, while also strengthening their comprehension of the concepts being learned. Additionally, this model plays an important role in sharpening critical thinking, communication, and collaboration skills, which are essential competencies for students' development in the modern era.